Pendampingan Masyarakat Mengenai Pemanfaatan Tanaman TOGA sebagai Pemenuhan Gizi di Kecamatan Kawali Kabupaten Ciamis: Community Assistance Regarding the Use of TOGA Plants to Fulfill Nutrition in Kawali District Ciamis Regency - Trinovani, Elvi; Kusmiyati, Mimin; Purkon, Dicki Bachtiar; Fatimah, Cucu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Fulfilling nutritional intake can be done by utilizing TOGA plants. TOGA plants have high nutritional content to support the fulfillment of daily nutritional needs. The aim of community service related to TOGA plants is to increase community understanding and access to nutritional sources needed to prevent high levels of malnutrition. The method used is Participatory Action and Learning and evaluated using pre-test and post-test methods. There was an increase in knowledge scores at the end of the training, namely an average of 15.8 points. The variation in knowledge scores on the pre-test tends to be higher than on the post-test, this shows that there is a similar perception of understanding of the material at the end of the training.